Exsanguination From Superficial Lower Extremity Trauma. (March 2022) - Prahlow, Samuel P.; Abadi, Arad; Prahlow, Joseph A.
Abstract : Abstract: Deaths related to exsanguination are not rare; however, most are related to large-caliber blood vessel or organ disruption. This article reports 2 deaths from external hemorrhage arising from superficial lower extremity trauma in persons with peripheral vascular disease and anticoagulant therapy. The first involved a 78-year-old woman who was found unconscious in her home by a relative, with a plastic bag tied around her left foot and evidence of profuse hemorrhage arising from a left great toenail partial avulsion injury. The second involved a 48-year-old male resident of an adult group home who was involved in a physical altercation with a group home employee, who reportedly kicked the decedent in the right shin, resulting in extensive hemorrhage and death. The cases highlight the fact that lethal exsanguination can occur from superficial trauma. Persons with peripheral vascular disease and those taking anticoagulants may be at particular risk for such deaths.